Correlatos da atividade física em crianças e adolescentes: um estudo piloto - Thiago Silva Piola; Eliane Denise Araújo Bacil; Priscila Iumi Watanabe; Tiago Rocha Alves Costa; Wagner Campos (Universidade Estadual do Oeste do Paraná, 2018)
Understanding the associated (correlated) factors to the sedentary behavior of children and adolescents is essential to promote an improvement in the interventions of physical activity programs. The aim of the study was to verify the association between physical activity and its correlates in children and adolescents. A total of 444 schoolchildren were analyzed, 214 boys and 230 girls aged 8 to 18 years. The analyzed variables were socioeconomic level, nutritional status, biological maturation, analyzed by somatic and sexual maturation, social support, self efficacy, sedentary behavior and level of physical activity. The results showed associations between the physical activity of the girls and the social support of the parents (OR: 0.12 CI95%: 0.04-0.31), between the physical activity of the boys and the social support of the friends (OR: 0.25 IC95%: 0.09-0.67). In conclusion, social support is associated with the practice of physical activities of boys and girls, and this correlate must be considered in future interventions.